USM PhD STUDENT WINS BEST POSTER AWARD IN JAPAN - MPRC, Pusat Media & Perhubungan Awam (USM, 2015)
PENANG, July 2015 A Doctoral (Ph.D) candidate from Universiti Sains Malaysia (USM), Ong Su Yean made the nation and USM proud when she was chosen as one of the winners for the Best Poster Award at the 7th International Conference on Green and Sustainable Chemistry (GSC7) and the 4th JACI/GSC Symposium in Tokyo, Japan, recently.